Building Airline Passenger Loyalty Through an Understanding of Customer Value: A Relationship Segmentation of Airline Passengers - Leick, Ryan (Cranfield University, 2007)
This thesis explores means of restoring profitability to the airline industry by cultivating intrinsically motivated brand loyalty between passengers and airlines in today’s fragile environment. The air transport industry is caught up in traditional transaction-based strategies. Airlines rely on archaic frequent flyer programs (FFPs) to maintain loyalty which deter customers from choosing alternative airlines by increasing the cost associated with switching. In contrast, other industries foster loyalty through relationship marketing to increase the customer’s value of the relationship. The objectives of this thesis are to 1) establish the link, if any, between passenger value, loyalty and increased airline profitability as well as 2) develop a competitive strategy for relationship marketing in the airline industry. The methodology comprises a ‘reverse value segmentation’ of passengers on value data collected in the New York – London market. The result is a model which segments customers into value profiles characterised by attitudes and behaviours towards loyalty. This dissertation extends the knowledge of passenger buying behaviour and choice as well as establishing passenger value as a foundation for strengthening industry structure. The results support a shift from the commoditized low-cost, no-frills model to a low-fare, ‘high-value’ model focusing on mass customization through CRM technologies.